The opacity of mind an integrative theory of self-knowledge - Carruthers, Peter, 1952- (Oxford : Oxford University Press, 2011)
Do we have introspective access to our own thoughts? Peter Carruthers challenges the consensus that we do: he argues that access to our own thoughts is always interpretive, grounded in perceptual awareness and sensory imagery.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes index.
Keywords: Self-knowledge, Theory of